1997
DOI: 10.1111/j.1528-1157.1997.tb01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Late Seizures and Their Role in Rehabilitation of Inpatients

Abstract: Summary:Purpose: This study was designed to (a) identify the prevalence of poststroke late seizures in a population of patients admitted to rehabilitation of neurologic sequelae of their first stroke, (b) recognize reliable prognostic factors associated with the occurrence of poststroke late seizures, and (c) evaluate the impact of seizures on the results of rehabilitation treatment.Methods: In a prospective study of 306 consecutive patients admitted to a rehabilitation hospital for sequelae of their first str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
2
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 23 publications
7
51
2
5
Order By: Relevance
“…1,[21][22][23] Despite the different design of these studies (mixed population of hemorrhagic and ischemic stroke), age below 65 years was revealed as a factor associated with seizures after ICH. Recently presented data on patient populations similar to ours also demonstrated an association of younger age with seizures.…”
Section: Discussionmentioning
confidence: 99%
“…1,[21][22][23] Despite the different design of these studies (mixed population of hemorrhagic and ischemic stroke), age below 65 years was revealed as a factor associated with seizures after ICH. Recently presented data on patient populations similar to ours also demonstrated an association of younger age with seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on small populations report varying results [Paolucci et al 1997;Bryndziar et al 2015]. Taken together, there may be room for improvement in management that should aim for seizure freedom in the same manner as in other forms of epilepsy.…”
Section: Aed Treatmentmentioning
confidence: 98%
“…This explains the low mean age (57 years) of our series. Other series reporting a higher seizure prevalence after striatocapsular infarcts included patients with a higher median age [6, 7, 14]. …”
Section: Discussionmentioning
confidence: 99%